An innovative method to optimize the maintenance policies in an aircraft: General framework and case study. (May 2015) - Regattieri, A.; Giazzi, A.; Gamberi, M.; Gamberini, R.
Abstract: Maintenance policies applied to aircrafts are governed by a mix of airworthiness authorities' regulations and choices of suppliers and users. This allows airlines to use different strategies to minimize the total costs of maintenance. In this paper, a new approach that integrates the failure and reparation processes, such as modelling, optimization algorithms, and simulation methods, is proposed to define the best maintenance strategies for complex systems. A case study of an airline carrier is presented. In particular, several critical components for the A320 aircraft family are considered. The impact of the spare parts inventory management is discussed. Different preventive maintenance policies are tested and simulated. With the new policies, the average availability of the aircraft is satisfactory and the total annual cost is reduced to a value of approximately 20% in comparison with the previous policies adopted by the company.